Czy ludzie szacują prawdopodobieństwa? - Kuśmierczyk, Paweł (Do people assess probabilities?, 2006)
The most of economic models describing the agents’ decision making process use the assumption that the agents base their decisions on the system of subjectively formed probabilities of future events. However it is a common belief that in reality people make most of their decisions without any assessment of future events’ probabilities. The paper tries to show that this common belief is false. The assessment of chances of future events, leading to the construction of (often imperfect) system of subjective probabilities, is not only being made but is fundamental to the agents’ decision making process.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1131, s. 230-238